Parallel quality assessment of emergency departments by European foundation for quality management model and Iranian national program for hospital evaluation. - Mohammad Hasan Imani Nasab; Bahram Mohaghegh; Nader Khalesi; Ebrahim Jaafaripooyan (Tehran University of Medical Sciences, 2013)
European Foundation for Quality Management (EFQM) model is a widely used quality management system (QMS) worldwide, including Iran. Current study aims to verify the quality assessment results of Iranian National Program for Hospital Evaluation (INPHE) based on those of EFQM.This cross-sectional study was conducted in 2012 on a sample of emergency departments (EDs) affiliated with Tehran University of Medical Sciences (TUMS), Iran. The standard questionnaire of EFQM (V-2010) was used to gather appropriate data. The results were compared with those of INPHE. MS Excel was used to classify and display the findings.The average assessment score of the EDs based on the INPHE and EFQM model were largely different (i.e. 86.4% and 31%, respectively). In addition, the variation range among five EDs' scores according to each model was also considerable (22% for EFQM against 7% of INPHE), especially in the EDs with and without prior record of applying QMSs.The INPHE's assessment results were not confirmed by EFQM model. Moreover, the higher variation range among EDs' scores using EFQM model could allude to its more differentiation power in assessing the performance comparing with INPHE. Therefore, a need for improvement in the latter drawing on other QMSs' (such as EFQM) strengths, given the results emanated from its comparison with EFQM seems indispensable.